Prevalence, Diagnostic Utility and Associated Characteristics of Bronchodilator Responsiveness - Richard Beasley; Rod Hughes; Àlvar Agustí; Peter M.A. Calverley; Bradley E. Chipps; Ricardo del Olmo; Alberto Papi; David Price; Helen K. Reddel; Hana Müllerová; Eleni Rapsomaniki (2023)
The prevalence and diagnostic utility of bronchodilator responsiveness (BDR) in a real-life setting is unclear.